(untitled) (Innovative professional education, 2024)
Today, Ukraine is one of the most energy-intensive economies in the world and has a huge potential for energy saving and energy efficiency, so it is necessary to introduce modern construction technologies, materials, increase the share of energy from renewable sources, reuse of resources, etc. The measures of the state in the field of energy efficiency are the popularization among the population of approaches to its improvement, in particular, the improvement of professional training of future construction workers by means of interactive pedagogical technologies.